Introdução à filosofia do direito matrimonial: a família - instituição sob proteção do Estado - Korte, Paulo Thomas (2009)
This work is a Master dissertation project that address the role of Law in the civil society, especially to reach and maintain the good of all, without prejudice of origin, race, sex, color, age and any other forms of discrimination (art.3, IV, da CF). The work speaks about the need to ensure the good of society through the good of the family, its primary cell. And, to ensure the good of the latter, it is necessary to guarantee the health of its core: the relationship between men and women. The law, especially the art. 1566 of the Civil Code, makes the role of regulating the passion manifestation limits of men and women in order to lead them to keep the good in the marriage contract